Comparative Studies on Wine Grapes on Different Trellising Systems: I. Consumptive Water Use - Van Zyl, J. L.; van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
A field trial involving four trellising systems viz.( a) Bush vines, (b) Perold, ( c) Lengthened Perold, (d) 1,7 m Slanting trellis, showed differences of the utmost importance with regard to rooting densities, consumptive water use and the incidence of Botrytis rot. Soil physical conditions were dominant in determining root distribution patterns. The slanting trellis had significantly more roots than the other systems. The consumptive water use, however, was not affected by amount of roots but mainly by the micro-climate. Contrary to expectation, the largest trellising system did not show the highest consumptive water use, but under the experimental conditions the bush vines had the fastest evapotranspiration rate. Average crop factors of 0,313; 0,260; 0,241 and 0,205 were found from bud burst to harvesting for bush vines, slanting trellis, lengthened Perold and Perold systems respectively. The high evapotranspiration rate of the bush vines is attributed to higher ambient air temperatures, more air movement as well as less shading of the soil surface than in the case of the slanting trellis. Crop factors varied according to soil moisture content, indicating the need to determine these parameters for specific irrigation frequencies. The low crop factors determined in this experiment emphasize the high water use efficiency of vineyards and stress the need to adopt existing crop factors to recent findings. Significant differences which cannot be attributed to micro-climate conditions occurred among trellising systems. Grape juice analyses, carried out throughout the growing season, indicated a relationship between total nitrogen and arginine status and Botrytis cinerea determined immediately prior to harvesting. More Botrytis rot was found at lower cropping levels. More investigations as to the relationship among the incidence of Botrytis rot, cropping level and nitrogen status of the plant are needed.